2017
DOI: 10.1021/jacs.7b01979
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Chemistry Targeting Proteins

Abstract: The specific recognition of protein surface elements is a fundamental challenge in the life sciences. New developments in this field will form the basis of advanced therapeutic approaches and lead to applications such as sensors, affinity tags, immobilization techniques, and protein-based materials. Synthetic supramolecular molecules and materials are creating new opportunities for protein recognition that are orthogonal to classical small molecule and protein-based approaches. As outlined here, their unique m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
137
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(137 citation statements)
references
References 112 publications
0
137
0
Order By: Relevance
“…These studies have demonstrated the breadth of chemical functionalities that can be matched with structural features on protein surfaces. In some cases, the binding of a supramolecular ligand leads to protein assembly . Such a “molecular glue” property has applications in the fabrication of advanced materials …”
Section: Introductionmentioning
confidence: 99%
“…These studies have demonstrated the breadth of chemical functionalities that can be matched with structural features on protein surfaces. In some cases, the binding of a supramolecular ligand leads to protein assembly . Such a “molecular glue” property has applications in the fabrication of advanced materials …”
Section: Introductionmentioning
confidence: 99%
“…[15,16,[19][20][21] Supramolecular building blocks are increasingly popular as receptors for protein binding and assembly. [12][13][14] Examples include protein oligomerization mediated by calixarenes [16] and foldamers. [17] Anionic calixarenes have proven particularly useful for the assembly of cationic proteins.…”
Section: Methodsmentioning
confidence: 99%
“…A central goal in supramolecular chemical biology1 is to generate ligands capable of solvent exposed protein‐surface recognition for the purpose of orthosteric protein–protein interaction (PPI) inhibition 2, 3, 4. Inhibition of PPIs is considered challenging in view of the fact that such interactions involve extended and less well‐defined surfaces than the “lock‐and‐key”‐like interfaces that have historically proven to be tractable targets for drug‐discovery 4.…”
Section: Introductionmentioning
confidence: 99%
“…A central goal in supramolecular chemical biology [1] is to generate ligands capable of solvent exposed protein-surface recognition for the purpose of orthosteric protein-protein interaction (PPI) inhibition. [2][3][4] Inhibition of PPIs is considered challenging in view of the fact that such interactions involve extended and less well-defined surfaces than the "lock-and-key"like interfaces that have historically proven to be tractable targets for drug-discovery. [4] Several supramolecular scaffolds have been explored as templates upon which to elaborate ligands for selective and high affinity protein-surface binding, [5] including: porphyrins, [6][7][8][9] calixarenes, [9][10][11][12][13] cucurbiturils, [14,15] molecular clips, [16,17] ruthenium(II) tris-chelates [18][19][20][21][22][23] and other ligands.…”
Section: Introductionmentioning
confidence: 99%